3D reconstruction of geomaterial microstructure based on differentiable descriptors - He, Zijie; Ning, Yu; Zhang, Yutao; Huang, Qingfu; Zhou, Yuang; Meng, Qingxiang (Frontiers in Physics, 2025)
The microstructure of geomaterials plays a crucial role in determining their physical and mechanical properties. The complex mechanical behavior of certain coarse-grained geomaterials significantly affects their resistance to deformation, making an accurate characterization of their internal structure essential. However, obtaining core samples of such materials is often costly and labor-intensive, whereas acquiring two-dimensional (2D) structural information is more feasible. This study presents a microstructure reconstruction technique based on a differentiable optimization framework, wherein the reconstruction process minimizes the error of a given descriptor while considering its derivative. The proposed method enables reconstruction using either a single 2D slice or three orthogonal 2D slices. Furthermore, the effectiveness of the 2D-to-3D reconstruction is validated through actual computed tomography (CT) scans of coarse-grained geomaterial samples collected from the Xinjiang region.